Dynamically reconfigurable command and control structure for network-centric warfare. (May 2015) - Pang, Chee Khiang; Mathew, Josey
The rapidly changing battle conditions in modern network-centric operations prescribe expectations for speedy deployment and nimble ad hoc reconfiguration of military networked teams. In this paper, a formal command and control (C2) structure is presented that allows for reliable ad hoc reconfiguration of tasks and resources of multiple simultaneous missions. Missions and assigned resources can be removed or added in an online manner without affecting other running missions. A mathematically justified software tool called the Reconfigurable Discrete Event Control (RDEC) is proposed by extending an existing framework using simple matrix decomposition. The RDEC effectively allows multiple fighting platforms of different interdisciplinary fields to join and leave the network easily in a "plug-and-play" manner. The proposed C2 structure is developed and demonstrated on a simulation study involving a Singapore armed forces team with three realistic attack missions. Extensive simulation results verify that the networked team is fairly sequenced and the missions and resources can be removed or added without blocking effects.